INTEGRASI NILAI-NILAI MULTIKULTURAL DALAM KURIKULUM PENDIDIKAN AGAMA ISLAM UNTUK MEMBANGUN TOLERANSI DI SEKOLAH - Tentiasih, Septyana; Rizal Rifa'i, Muhammad (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2022)
This study aims to examine the integration of multicultural values into the Islamic Religious Education (PAI) curriculum as a means of fostering tolerance in schools. The research employs a qualitative method with a library research approach, focusing on several schools in Indonesia that have implemented a multicultural-based PAI curriculum. The findings indicate that integrating multicultural values into PAI enhances students' understanding and tolerance toward religious and cultural diversity. The appropriate implementation of the curriculum, including the use of collaborative learning methods and relevant teaching materials, has proven effective in shaping students' inclusive character and appreciation for differences. However, the study also identifies several challenges, such as the lack of teacher training in delivering multicultural values and resistance to curriculum changes. Despite these challenges, the research highlights that integrating multicultural values into the PAI curriculum has significant potential to create a harmonious school environment and promote the development of a more tolerant society.